Liquid atomic layer deposition as emergent technology for the fabrication of thin films. Issue 19 (1st April 2021) - Graniel, Octavio; Puigmartí-Luis, Josep; Muñoz-Rojas, David
Abstract : Liquid atomic layer deposition (LALD) has emerged as a complementary technology of atomic layer deposition (ALD) to help overcome some of the challenges currently faced from working in the gas-phase. Abstract : Atomic layer deposition (ALD) is widely recognized as a unique chemical vapor deposition technique for the fabrication of thin films with high conformality and precise thickness control down to the Ångstrom level, thereby allowing surface and interface nanoengineering. However, several challenges such as the availability of chemical precursors for ALD and the use of vacuum conditions have hampered its widespread adoption and scalability for mass production. In recent years, the liquid phase homolog of ALD, liquid atomic layer deposition (LALD), has emerged as a much simpler and versatile strategy to overcome some of the current constraints of ALD. This perspective describes the different strategies that have been explored to achieve conformality and sub-nanometer thickness control with LALD, as well as the current challenges it faces to become a part of the thin-film community toolbox, in particular its automation and compatibility with different types of substrates. In this regard, the important role of LALD as complementary technology to ALD is emphasized by comparing the different pathways to deposit the same material and the precursors used to do so.